2015
DOI: 10.1128/jvi.01876-15
|View full text |Cite
|
Sign up to set email alerts
|

Fitness-Balanced Escape Determines Resolution of Dynamic Founder Virus Escape Processes in HIV-1 Infection

Abstract: To understand the interplay between host cytotoxic T-lymphocyte (CTL) responses and the mechanisms by which HIV-1 evades them, we studied viral evolutionary patterns associated with host CTL responses in six linked transmission pairs. HIV-1 sequences corresponding to full-length p17 and p24 gag were generated by 454 pyrosequencing for all pairs near the time of transmission, and seroconverting partners were followed for a median of 847 days postinfection. T-cell responses were screened by gamma interferon/inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 67 publications
(88 reference statements)
0
23
0
Order By: Relevance
“…It is important to note that viral escape was detected in some but not all of the initially targeted epitopes. This phenomenon has been previously described and studied by several groups (e.g., [ 29 , 58 , 60 ]), and is likely influenced by host (e.g., genetic background, magnitude/quality of CTL response) and viral factors (e.g., genetic barrier to escape, viral fitness, capacity of targeted protein accommodate sequence change).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is important to note that viral escape was detected in some but not all of the initially targeted epitopes. This phenomenon has been previously described and studied by several groups (e.g., [ 29 , 58 , 60 ]), and is likely influenced by host (e.g., genetic background, magnitude/quality of CTL response) and viral factors (e.g., genetic barrier to escape, viral fitness, capacity of targeted protein accommodate sequence change).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, while in some participants CTL escape proceeded as the pVL remained virtually unchanged (e.g., 40100), in other cases we noticed a transient and modest increase of pVL, coinciding with a change in dominance of escape variants (e.g., 20225). Among the possible causes for this are: a) differences in fitness between WT and escape variants, and among escape variants [ 58 ], and b) the emergence of new CTL clonotypes with broader variant recognition [ 59 ]. The underlying mechanism linking pVL dynamics with CTL escape and the change in escape dominance warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…Deep sequencing revealed that this mutation was strongly selected against and was found at very low frequency by 29 wpi. Sunshine et al showed that dynamic escape processes only resolve with the selection of mutations that confer escape with little/no fitness cost to the virus (30). We showed there was no replicative fitness cost incurred by incorporation of the 392 6(392NXT-) deletion, suggesting other pressures such as ADCC-mediating antibodies played a role in controlling viral populations through constraining nAb escape pathways.…”
Section: Discussionmentioning
confidence: 58%
“…This was also observed for 5/8 participants (all except F4, F5, and F8) in the gag phylogram ( S2 Fig ) and was also previously observed for individuals within the MACS cohort [ 60 ]. While the branch lengths separating sequences from different individuals are long, and may result in rooting artefacts, such topologies are consistent with the acquisition of reversion of immune escape mutations acquired from the transmitting partner in the early years of infection [ 61 66 ]. Further departure from the MRCA then appears to dominate, due to host-specific escape mutations.…”
Section: Resultsmentioning
confidence: 79%